Handbook of bereavement : theory, research, and intervention - Stroebe, Margaret S.; Stroebe, Wolfgang; Hansson, Robert O. (Cambridge University Press, 1993)
The Handbook of Bereavement constitutes a comprehensive review of scientific knowledge on the consequences of losing a loved person through death. The volume brings into focus a wide variety of theoretical approaches that have recently been incorporated into bereavement research. Physiological changes associated with the mental and physical consequences of bereavement, where significant advances in knowledge have recently been made, are surveyed. The phenomenology of grief, distinctions between normal and pathological grief, as well as measurement and assessment techniques, are given detailed coverage. Chapters document not only detrimental effects to mental and physical health, but a much broader range of consequences associated with loss. They explore the relative vulnerability and coping styles of different individuals and groups. Analyses also go beyond the consideration of marital bereavement to reflect upon many different types of loss, including the special cases of bereavement among AIDS survivors and Holocaust survivors. Evaluations are provided of the availability and efficact of the different kinds of support for bereaved people, ranging from informal help to self-help groups to various counseling and therapy intervention programs. The Handbook of Bereavement brings together an international, interdisciplinary group of scholars to report research and explore key issues on the topic of bereavement. Focusing on methodologically sound, theoretically oriented, and empirically derived knowledge, the authors provide a structured framework for researchers and practitioners.